2021
DOI: 10.21037/atm-21-3301
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 and PTPRC are regulators of tumor microenvironment and potential prognostic biomarkers of lung adenocarcinoma

Abstract: Background: Tumor microenvironment (TME) plays an essential role in lung adenocarcinoma (LUAD) development and metastasis. With the development of TME research, it has been proved that differences in tumor-infiltrating immune cells (TICs) and gene expression profile are related to the prognosis of cancer.The aim of our study was to identify key genes affecting immune state in TME of LUAD. Methods:The RNA-seq data and clinical characteristics of 594 LUAD patients were downloaded from the TCGA database. ImmuneSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [31]. PTPRC was identified as Parkinson's disease biomarker [32] and in lung adenocarcinoma, latent tuberculosis, and ovarian cancer, PTPRC served as a key hub gene and was highly associated with disease [33][34][35]. These results suggest that the constructed LASSO model could provide valuable clues for researchers Computational and Mathematical Methods in Medicine to identify key AD-related diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [31]. PTPRC was identified as Parkinson's disease biomarker [32] and in lung adenocarcinoma, latent tuberculosis, and ovarian cancer, PTPRC served as a key hub gene and was highly associated with disease [33][34][35]. These results suggest that the constructed LASSO model could provide valuable clues for researchers Computational and Mathematical Methods in Medicine to identify key AD-related diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…PTPRC, also known as CD45, expressed on nucleated cells of the hematopoietic system, is an essential regulator of B- and T-cell receptor signaling ( 21 , 22 ). In recent years, many studies have reported that CD45 had promoted the development of diabetes and its metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis demonstrated that PTPRC, CD53, IRF8, IL10RA, and LAPTM5 perhaps have the essential functions in molecular mechanisms of DN. PTPRC, also known as CD45, expressed on nucleated cells of the hematopoietic system, is an essential regulator of B-and Tcell receptor signaling (21,22). In recent years, many studies have reported that CD45 had promoted the development of diabetes and its metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins exhibiting a decrease, ICAM-1 (encoded by Icam1 ) represents an adhesive molecule also known to weaken the immune response in cancer cells in addition to its promoting action on cancer progression [ 73 ]. The protein tyrosine phosphatase CD45 (encoded by Ptprc ) was shown to affect the function of T and other immune cells, with a negative impact on the prognosis of lung adenocarcinoma [ 74 ].…”
Section: Discussionmentioning
confidence: 99%